Acne patients frequently associated with abnormal plasma lipid profile. Issue 3 (13th January 2015) - Jiang, Hao; Li, Chang Yi; Zhou, Lu; Lu, Bin; Lin, Yinghui; Huang, Xiaoqi; Wei, Bin; Wang, Qiang; Wang, Leping; Lu, Jianqi
Abstract This study was designed to investigate the relationship between plasma lipid profile and acne. Acne patients (n = 181) and healthy volunteers (n = 130) matched in terms of both age and sex were enrolled. Plasma total cholesterol (TC), triglyceride (TG), high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol (LDL‐C) and lipoprotein (LP)(a) levels were measured. TC, LDL‐C and LP(a) levels in male and female patients with severe acne were significantly higher than in the healthy control group (P < 0.05). TG in male patients with severe and moderate acne was significantly higher than in the healthy control group (P < 0.05). LP(a) in male and female patients with mild, moderate and severe acne was significantly higher than in the healthy control group (P < 0.05). The constituent ratio of male and female patients with TC, TG, LDL‐C and LP(a) over the normal range was signi‐ficantly higher than in the healthy control group. In this study, acne patients were frequently associated with abnormal lipid profile, providing a new basis for further exploration of the pathogenesis, as well as new treatments, of acne vulgaris.